The impact of changes in tax rates and prices consolidated budget and production development - V. V. Tyugay (Путеводитель предпринимателя)
The article considers the impact of changes in tax rates on income in the consolidated budget and the development of production, as well as the results of the study according to the cash inflow in the consolidated budget and economic condition of the manufacturers from the value of the tax rate on profits.